Nationality Between Poststructuralism and Postcolonial Theory - Leonard, P. author. aut Link
VII, 198 p.
Keywords: Nationality Between Poststructuralism and Postcolonial Theory: A New Cosmopolitanism examines and interrogates recent work on nationality in literal, critical and cultural theory. Focusing on the work of Derrida, Deleuze and Guattari, Kristeva, Spivak, and Bhabha, it explores how, for these theorists, the concepts of community, the new International, nomadism, deterritorialization, cosmopolitanism, hospitality, the native informant, hybridity and postcolonial agency can provoke a different understanding of national identity.